The Effect of Online and Offline Blended Teaching on Iranian EFL Learners’ Reading Comprehension: A Study Across Proficiency Levels - Hakimi Asl , Maryam; Mohammadi, Vali; Abdi, Reza (Assessment and Practice in Educational Sciences, 2024)
The objective of this study was to investigate the effect of online and offline blended teaching on Iranian EFL learners’ reading comprehension across proficiency levels. A sequential mixed-methods design was employed, combining quantitative and qualitative phases. Sixty Iranian upper-intermediate EFL learners, aged between 18 and 34, were selected through convenience sampling and divided into two groups: an experimental group (n=30) that received blended instruction integrating online and offline tasks, and a control group (n=30) that received traditional face-to-face instruction. The Oxford Placement Test was used to homogenize participants, followed by the administration of a reading comprehension pretest and posttest. The intervention lasted for eight sessions, after which posttests and delayed posttests were conducted. Additionally, semi-structured interviews were administered to a subset of participants in the experimental group to explore their perceptions of blended learning. Quantitative data were analyzed using descriptive statistics and independent samples t-tests, while qualitative data were examined through thematic analysis. The independent samples t-test revealed no significant difference between the two groups at the pretest stage, confirming comparability in their initial proficiency. However, the posttest results showed a statistically significant difference in favor of the experimental group (t(58)=2.479, p<.001), with learners in the blended instruction group achieving higher reading comprehension scores compared to those in the control group. These results demonstrate the effectiveness of blended teaching in enhancing reading comprehension among Iranian EFL learners. The study concludes that blended teaching significantly improves reading comprehension performance compared to traditional methods. While learners expressed positive perceptions of blended instruction, they also reported challenges related to technical issues, limited feedback in writing and grammar, and concerns about its use in assessment contexts. Overall, blended teaching can be considered a promising pedagogical approach in Iranian EFL settings, provided that contextual and technological challenges are adequately addressed.